ETNOMATEMATIKA BATIK JONEGOROAN DITINJAU DARI ASPEK LITERASI MATEMATIS - Susanti, Seftyana Ayu; Budiarto, Mega Teguh (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
Mathematical literacy and ethnomatematics are two main ideasÂ to determine the role ofÂ mathematics in everyday life. Mathematical literacy is an idea that focuses on mathematical and social requirements that can reflect a person's competence in mathematics, while ethno-mathematics emphasizes the competence of people developed in different cultural groups in everyday life. This research focuses on the Jonegoroan batik culture (batik typical of Bojonegoro Regency) because no previous researchers have studied it, especially about ethno-mathematics and mathematical literacy. The purpose of this study was to describe the ethnomatematic form of Jonegoroan batik in terms of mathematical literacy aspects, namely aspects of the content, context, and mathematical processes. This type of research is qualitative research with an ethnographic approach. Data collection was carried out by means of participant observation and interviews. The instruments used were observation sheets, interview guidelines, and research note sheets. The data analysis technique used triangulation. The results of this study indicate that based on ethnomatematic studies on Jonegoroan batik, several mathematical concepts can be found, namely the concept of geometric transformation,Â two-dimentional figure, and graphs of trigonometric functions. Based on these studies, the activities carried out by Jonegoroan batik craftsmen fulfill the aspects of mathematical literacy. Thus, Jonegoroan batik can be used as a medium for learning mathematics.